A two‐way relay framework based on interference cancellation in wireless networks. Issue 6 (13th January 2015) - Fu, Gowin; Li, Li; Hu, Honglin; Du, Yang
Abstract: The two‐way relay (TWR) protocols are efficient in providing appreciable throughput gains in wireless networks through the use of network coding to combine packets from multiple channels. The key determinant factor in driving the throughput improvement is the degree of simultaneity achieved in the relay scheme. In this paper, we propose a new TWR protocol named interference cancellation TWR (IC‐TWR), which combines network coding, spatial diversity, and IC techniques to arrive at high degree of simultaneity and in the meanwhile to relax the requirement on channel state information as compared with TWR schemes based on amplify‐and‐forward. Numerical analysis shows that the proposed IC‐TWR is uniformly advantageous over the traditional decode‐and‐forward scheme in terms of system throughput and end‐to‐end delay. The proposed scheme may be useful for system designers of high‐speed multimedia applications in wireless mobile networks, wireless cellular networks, wireless sensor networks, and so on. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this manuscript we propose a new two‐way relay protocol named IC‐TWR winch combines network coding, spatial diversity, and interference cancellation techniques to arrive at high degree of simultaneity, and in the meanwhile to relax the requitement on channel state information (CSI) as compared with TWR schemes based on Amplify‐and‐Forward (AF). Numerical analysis shows that the proposed IC‐TWR is uniformly advantageous over the traditional Decode‐and‐Forward (DF) scheme in terms of system throughput and end‐to‐end delay.